2022
DOI: 10.5194/nhess-2022-196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The OBS noise due to deep ocean currents

Abstract: Abstract. Ocean bottom seismometers (OBS) are usually deployed for seismological investigations but these objectives are impaired by noise resulting from ocean environment. We split the OBS recorded seismic noise into three domains, short-period, microseisms and long-period, also known as tilt-noise. We show that the first and third domains are controlled by bottom currents but these are not always a function of the tidal forcing. Instead we suggest that the ocean bottom has a flow regime resulting from two po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Several recent studies attempted to model the harmonic noise generated by the head-buoy and rope strumming in the water columns of the DEPAS OBSs (Stähler et al, 2018;Essing et al, 2021b;Corela et al, 2022); however, this was observed at frequencies between 1 and 10 Hz. For example, Stähler et al (2018) modeled the strumming of the rope and head buoy as it is usually implemented in the Lobsters of the DEPAS pool, including in our deployment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies attempted to model the harmonic noise generated by the head-buoy and rope strumming in the water columns of the DEPAS OBSs (Stähler et al, 2018;Essing et al, 2021b;Corela et al, 2022); however, this was observed at frequencies between 1 and 10 Hz. For example, Stähler et al (2018) modeled the strumming of the rope and head buoy as it is usually implemented in the Lobsters of the DEPAS pool, including in our deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of short-period (≤ 0.2 s or ≥ 0.5 Hz) noise can be geological (e.g., local earthquakes, volcanic tremors, etc.) or due to the interaction of sea-bottom currents with the structural components of the OBS (Corela et al, 2022). In addition, noise due to passing ships and marine mammals must be considered.…”
Section: Short-period Rangesmentioning
confidence: 99%